2016
DOI: 10.1186/s12885-016-2504-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of quality of life score in disease-free survivors of surgically-treated lung cancer

Abstract: BackgroundWe aimed to evaluate the prognostic value of quality of life (QOL) for predicting survival among disease-free survivors of surgically-treated lung cancer after the completion of cancer treatment.MethodsWe administered the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30), the Quality of Life Questionnaire Lung Cancer Module (QLQ-LC13), Hospital Anxiety and Depression Scale (HADS), and Posttraumatic Growth Inventory (PTGI) to 809 survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 42 publications
0
45
1
Order By: Relevance
“…In the context of cancer survivors, side effects of cancer and its treatment [11,12,18], financial concerns [16,19], distress over recurrence [19], family-related distress [19] have been found to affect survivors' QOL. It is an important predictor in outcomes of the disease and its treatment [20] and one of the indicators of adjustment in cancer survivors [12]. It is therefore crucial to understand and address not only the immediate but also the long-term medical and psychosocial issues that confront cancer survivors as they transit across the survivorship trajectory in order to enhance coping skills and improve their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of cancer survivors, side effects of cancer and its treatment [11,12,18], financial concerns [16,19], distress over recurrence [19], family-related distress [19] have been found to affect survivors' QOL. It is an important predictor in outcomes of the disease and its treatment [20] and one of the indicators of adjustment in cancer survivors [12]. It is therefore crucial to understand and address not only the immediate but also the long-term medical and psychosocial issues that confront cancer survivors as they transit across the survivorship trajectory in order to enhance coping skills and improve their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…PRO measures can give us a more accurate picture of patients' clinical status, allowing for early intervention. For example, studies have shown that changes in QoL scores are independent predictors of survival in patients with lung cancer [10]. In addition to better informing clinicians on the postoperative course of their patients, PRO measures can provide cardiothoracic surgeons with quality information to help patients make treatment-related decisions.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of both retrospective and prospective studies have similarly examined PRO and HRQoL results after operation for thoracic malignancies [2,10,[30][31][32][33][34][35][36][37]. A summary of select studies that examined PROs after lung cancer operation is shown in Table 2.…”
Section: Patient-reported Outcomes In Cardiothoracic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Although early detection, diagnosis and targeted therapy of NSCLC have made great progress, the five-year survival rate is still very low (3). Regional or distant metastasis is a risk factor for relapse and poor prognosis of NSCLC (3). However, there are currently no effective biomarkers to predict poor prognosis in NSCLC (4).…”
Section: Introductionmentioning
confidence: 99%